Apps for Children with Disabilities: Effectiveness of Mobile Health Technology for Adherence and Engagement with Home Therapy Programmes - Johnson, Rowan Winston (Curtin University, 2024)
This thesis investigated the use of a commercially available therapy prescription app to deliver home programmes for children with disabilities in a randomised controlled trial. With no improvements in program adherence, and feedback from the children that the app was boring, a new gamified therapy app, Zingo, was then developed and tested specifically for children. The Zingo app was found to be fun and motivating for children with disabilities.